2018
DOI: 10.1128/aac.00164-18
|View full text |Cite
|
Sign up to set email alerts
|

Source of the Fitness Defect in Rifamycin-Resistant Mycobacterium tuberculosis RNA Polymerase and the Mechanism of Compensation by Mutations in the β′ Subunit

Abstract: is a critical threat to human health due to the increased prevalence of rifampin resistance (RMP). Fitness defects have been observed in RMP mutants with amino acid substitutions in the β subunit of RNA polymerase (RNAP). In clinical isolates, this fitness defect can be ameliorated by the presence of secondary mutations in the double-psi β-barrel (DPBB) domain of the β' subunit of RNAP. To identify factors contributing to the fitness defects observed , several RNA transcription assays were utilized to probe in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 49 publications
6
37
0
Order By: Relevance
“…6 suggest that termination could play a role in rif resistance, consistent with the observed changes in termination caused by mutations at the D516, H526, and I572 residues of rpoB (70). These findings may relate to rif resistance in M. tuberculosis (50), as recent work in that organism has implicated termination efficiency as the mechanism underlying the cost of resistance (51).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…6 suggest that termination could play a role in rif resistance, consistent with the observed changes in termination caused by mutations at the D516, H526, and I572 residues of rpoB (70). These findings may relate to rif resistance in M. tuberculosis (50), as recent work in that organism has implicated termination efficiency as the mechanism underlying the cost of resistance (51).…”
Section: Discussionsupporting
confidence: 68%
“…We expect transcriptional profiles to be predictive of collateral sensitivity, as has been shown for chemogenomic profiles (49), to the extent that both reflect the molecular mechanisms underlying adaptation and the cost of resistance. These efforts may offer another avenue to manage resistance in bacterial infections that are treated with rif, such as Mycoplasma tuberculosis (50,51). Our approach to find extreme antagonistic gene-drug pairs is scalable and can facilitate the systematic design of antagonistically interacting drug combinations by providing targets-the gene mutations-against which a second drug may be developed.…”
Section: Introductionmentioning
confidence: 99%
“…L452P confers only low-level rifampin resistance, whereas mutations at position 435 (including D435Y and D435G) are associated with distinctly higher rifampin MICs (50), and in LAM4/KZN acquisition of D435G likely augmented rifampin resistance versus the L452P single mutant (51). Recent studies have implicated changes in protein stability (52) and transcriptional efficiency (53) as important determinants of how putative compensatory mutations impact fitness in rifampin-resistant Mtb . Although in our analysis D435G and I1106T only partially offset the destabilizing effects of L452P, multiple studies suggest that the compensatory effects of D435G may not be related exclusively to its effects on protein stability.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1 , I491V, also reported by Comas et al (2011) , is located at the interface between the α and β’ subunits; A734V is near the interface between the β and β’ subunits; G594E maps to a region between the two α helices, and the substitution of glycine with glutamate changes the charge of the side chain from neutral to negative. Interestingly, Stefan et al recently reported similar findings that F452L and V483G, two mutants of RpoC near I491V, displayed a compensatory effect on RpoB S450L mutated RNA polymerase in vitro by recovering the defects of open-promoter complex stability and elongation rate, enhancing termination efficiency and RNA primer hydrolysis ( Stefan et al, 2018 ). Their work demonstrates the possibility of and underlying mechanism of mutations in RpoC compensating for functional defects of RNA polymerase resulting from mutations in RpoB.…”
Section: Resultsmentioning
confidence: 88%